Prophetic Competence in Prospective Teacher Students at Muhammadiyah Metro University (Analytic Study) - Umi Hartati; Friska Octavia Rosa (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
The aim of this research is to determine the prophetic competence and the average percentage of each aspect of prophetic competence among prospective teacher students at Muhammadiyah University Metro. This research uses a descriptive analytical method, with research subjects consisting of students from Muhammadiyah University Metro in the education department. Data collection is done through a questionnaire survey, and the data analysis is qualitative and inductive, while the data analysis technique is triangulation. The results of this research show that the percentage analysis of prophetic competence based on the research instrument indicates that Shidig competence obtained 52.03% and falls into the high criteria, Amanah competence obtained 33.5% and falls into the low criteria, Fathonah competence obtained 65.08% and falls into the moderate criteria, and Tabligh competence obtained 47.7% and falls into the low criteria.